A Ligand Selection Strategy Identifies Chemical Probes Targeting the Proteases of SARS‐CoV‐2. Issue 12 (28th January 2021) - Peñalver, Lilian; Schmid, Philipp; Szamosvári, Dávid; Schildknecht, Stefan; Globisch, Christoph; Sawade, Kevin; Peter, Christine; Böttcher, Thomas
Abstract: Activity‐based probes are valuable tools for chemical biology. However, finding probes that specifically target the active site of an enzyme remains a challenging task. Herein, we present a ligand selection strategy that allows to rapidly tailor electrophilic probes to a target of choice and showcase its application for the two cysteine proteases of SARS‐CoV‐2 as proof of concept. The resulting probes were specific for the active site labeling of 3CL pro and PL pro with sufficient selectivity in a live cell model as well as in the background of a native human proteome. Exploiting the probes as tools for competitive profiling of a natural product library identified salvianolic acid derivatives as promising 3CL pro inhibitors. We anticipate that our ligand selection strategy will be useful to rapidly develop customized probes and discover inhibitors for a wide range of target proteins also beyond corona virus proteases. Abstract : Tuning the ligand space allows to rapidly customize chemical probes for efficacy and active site specificity for a protease of interest. The application of this ligand selection approach is exemplified by generating probes for the two non‐homologous yet essential proteases of the new corona virus SARS‐CoV‐2 providing complementary chemical tools for proteomic labeling and inhibitor discovery.